Redefining natural abdominal anatomy in abdominoplasty using conventional liposuction: A prospective study - Leonardo Milanesi Possamai; Márcia Rodrigues Terres; Flávio Maciel de Freitas; Pedro Bins Ely; Níveo Steffen (Revista Brasileira de Cirurgia Plástica, 2019)
Introduction: Abdominoplasty techniques have constantly evolved since 1899. With modern liposuction techniques, the concept of high-definition liposuction aims to correct stigmas secondary to the procedure, such as a "tense" appearance and lack of natural abdominal convexity and concavity. Methods: Here we propose a technique to redefine the natural abdominal anatomy using traditional lipoabdominoplasty with selective liposuction to achieve more natural-looking surgical results that are reproducible for most patients. This study included 21 abdominoplasty procedures using the described technique performed between November 2018 and May 2019. The technique showed satisfactory ability to achieve a natural abdominal appearance using deep and superficial liposuction in abdominal shadow areas. Conclusion: The study showed that the technique is safe from a vascular point of view and reproducible due to the use of conventional liposuction, which is available to the vast majority of plastic surgeons.